Pengenceran Cairan Fermentasi Bonggol Pisang (Musa paradisiaca) Untuk Meningkatkan Pertumbuhan Rumput Laut Kappaphycus alvarezii - Samsu Adi Rahman; Muhammad Safir; Akbar Marzuki Tahya (Universitas Mataram, 2024)
Fermented liquid from banana weevils is a fermentation product involving banana weevils and microorganisms originating from the banana weevil itself. This fermented liquid contains nutrients and other compounds that have the potential to stimulate growth and control disease in seaweed. The aim of this research is to determine the effectiveness of administering banana weevil fermented liquid on the growth of Kappaphycus alvarezii seaweed. This research was carried out in the waters of Jayabakti Village, Pagimana District, Banggai Regency. This study used a completely randomized design with four treatments and three replications, namely A (control), B (1 L fermentation liquid/50 L seawater), C (1 L fermentation liquid/100 L seawater), and D (1 L fermentation liquid/150 L seawater). The test seaweed is immersed for one hour according to the dilution of each treatment. The parameters observed include absolute growth, daily specific growth, and water quality. The results showed that the dose of banana weevil fermentation liquid significantly affected the growth of seaweed. The highest average growth value was achieved in treatment B (1 L fermentation liquid/50 L seawater) with a daily growth rate of 3.07 ± 0.04% and absolute growth of 90.48 ± 1.51 g. This research shows that immersion in fermentation liquid in fermentation liquid for one hour can increase seaweed growth, with the best results at a dilution of 1 L of fermentation liquid/50 L of seawater.